Depression and chronic renal patients on hemodialysis: associated factors - Carolina Renz Pretto; Marina Brites Calegaro da Rosa; Cátia Matte Dezordi; Sabrina Azevedo Wagner Benetti; Christiane de Fátima Colet; Eniva Miladi Fernandes Stumm
ABSTRACT Objective: to verify the association of sociodemographic and clinical variables, life habits and functional capacity with symptoms indicative of depression in chronic renal patients on hemodialysis. Method: cross-sectional study developed from February to October of 2017 with 183 patients undergoing hemodialysis in two renal units located in the state of Rio Grande do Sul. Data collected with clinic and sociodemographic questionnaire and Beck Depression Inventory. Analysis with descriptive and analytical statistics and the chi-square test. Results: 55.2% of participants were elderly, 66.4% men, 90.7% retired, and 60.3% presented depressive symptoms. An association was found between symptoms indicative of depression and the female sex, greater number of comorbidities and post-hemodialysis intercurrences, emotional and physical symptoms, inactivity, failing to perform usual activities and the need for assistance in day-to-day. Conclusion: depressive symptoms are associated with burden of comorbidities, greater number of disease complications, hemodialytic intercurrences and functional dependence. Physical exercise practice can be an effective care strategy.